14-3-3σ (sigma) regulates proliferation and differentiation of multipotent p63-positive cells isolated from human breastmilk - Thomas, E.; Zeps, Nikolajs; Cregan, M.; Hartmann, P.; Martin, T. (2011)
The mammary gland is a dynamic organ that only undergoes complete differentiation during pregnancy. Differentiation is fuelled by asymmetric division of stem cells that reside in normally quiescent niches in the resting gland in response to pregnancy-associated hormones. Loss of regulation of stem cells is believed to underlie some breast cancers. This process is poorly understood in humans since it is difficult to extract stem cells from the lactating gland. We have identified a p63-positive population in breastmilk that proliferates and differentiates into at least two separate mammary lineages in culture. Nuclear translocation of p63 coincides with expression of the cell-cycle arrest protein 14-3-3σ (Sigma) and precedes differentiation. Transient down-regulation of Sigma promotes maintenance of the p63-positive population without affecting normal differentiation. We propose that p63-postive cells from breastmilk represent a novel source of cells to model regulation of mammary gland development and tumorigenesis.